(-x-9i)(x-9i)=0

Simple and best practice solution for (-x-9i)(x-9i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-x-9i)(x-9i)=0 equation:


Simplifying
(-1x + -9i)(x + -9i) = 0

Reorder the terms:
(-9i + -1x)(x + -9i) = 0

Reorder the terms:
(-9i + -1x)(-9i + x) = 0

Multiply (-9i + -1x) * (-9i + x)
(-9i * (-9i + x) + -1x * (-9i + x)) = 0
((-9i * -9i + x * -9i) + -1x * (-9i + x)) = 0

Reorder the terms:
((-9ix + 81i2) + -1x * (-9i + x)) = 0
((-9ix + 81i2) + -1x * (-9i + x)) = 0
(-9ix + 81i2 + (-9i * -1x + x * -1x)) = 0
(-9ix + 81i2 + (9ix + -1x2)) = 0

Reorder the terms:
(-9ix + 9ix + 81i2 + -1x2) = 0

Combine like terms: -9ix + 9ix = 0
(0 + 81i2 + -1x2) = 0
(81i2 + -1x2) = 0

Solving
81i2 + -1x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add 'x2' to each side of the equation.
81i2 + -1x2 + x2 = 0 + x2

Combine like terms: -1x2 + x2 = 0
81i2 + 0 = 0 + x2
81i2 = 0 + x2
Remove the zero:
81i2 = x2

Divide each side by '81'.
i2 = 0.01234567901x2

Simplifying
i2 = 0.01234567901x2

Take the square root of each side:
i = {-0.111111111x, 0.111111111x}

See similar equations:

| -38=-18-9 | | F(x)=1n(x-2)-4 | | x(3)+9=27 | | X^2+3=5x(x+6) | | 4(3+m)=8(6m+7) | | (x+9i)(x-9i)=0 | | 4x+7=22-x | | 7z-1=z+22 | | 3v+2y=100 | | 6cosx=4sinx | | (-x-9i)(x+9i)=0 | | -5x-1=29+5x | | -4y+7x=-24 | | 7x-(3+4x)= | | 3a-15=-14 | | 3c+18=14 | | 3r^2+25r+8=0 | | 14x-29=6x+29 | | C=.15M+15 | | 57+66+x=180 | | 1/8logx=-5/3 | | 13-2x=93 | | -5(3x-9)=150 | | 66+x+x=180 | | 1/2X-10=6 | | y^2-8y=20 | | 9x-2=98 | | (-4i)(2i)(-3i)= | | 6/5÷5/8 | | 7(d+2)=2(d-7)+5d | | 2X+Y=356 | | 7xy*9=0 |

Equations solver categories